A transcriptional toolbox for exploring peripheral neuroimmune interactions. Issue 9 (September 2020) - Liang, Zhi; Hore, Zoe; Harley, Peter; Uchenna Stanley, Federico; Michrowska, Aleksandra; Dahiya, Monica; La Russa, Federica; Jager, Sara E.; Villa-Hernandez, Sara; Denk, Franziska
Abstract : Abstract: Correct communication between immune cells and peripheral neurons is crucial for the protection of our bodies. Its breakdown is observed in many common, often painful conditions, including arthritis, neuropathies, and inflammatory bowel or bladder disease. Here, we have characterised the immune response in a mouse model of neuropathic pain using flow cytometry and cell-type-specific RNA sequencing (RNA-seq). We found few striking sex differences, but a very persistent inflammatory response, with increased numbers of monocytes and macrophages up to 3 1/2 months after the initial injury. This raises the question of whether the commonly used categorisation of pain into "inflammatory" and "neuropathic" is one that is mechanistically appropriate. Finally, we collated our data with other published RNA-seq data sets on neurons, macrophages, and Schwann cells in naive and nerve injury states. The result is a practical web-based tool for the transcriptional data mining of peripheral neuroimmune interactions. http://rna-seq-browser.herokuapp.com/ Abstract : Supplemental Digital Content is Available in the Text.The immune response to peripheral nerve ligation in mice is very long-lasting and differs between nerve and DRG. Interrogate the data yourself here: http://rna-seq-browser.herokuapp.com/.